The Philippine cabotage law: A case for policy review and formulation - Menaje, Placido M., Jr. (Animo Repository, 2014)
As an archipelago of 7,107 islands, the Philippines has a total coastline length of 36,289 kilometers, the fourth longest coastline in the world after Canada, Indonesia, and Russia. This number of islands and length of coastline make the country an excellent location for domestic and foreign maritime shipping. For a long time. however, domestic shipping in the country has been dominated by few shipping lines that charge high tariffs for both passengers and cargoes when tariff rates were deregulated. Business engaged in import-export transactions, farmers, forwarders of agricultural products, and local manufacturers point to the expensive cost of trading as the main reason for their reduced revenues. Local and foreign businessmen are of the opinion that the local shipping industry is inefficient and should be stimulated by allowing foreign-flagged vessels to compete with local shipping lines. This, however, will not be possible unless the Philippine Cabotage Law, which prohibits foreign-flagged vessels to engage in domestic shipping, is repealed. During his 4th state of the nation address on July 26, 2013, Philippine President Benigno S. Aquino III talked about the possibility of amending the said law.This paper revisits the cabotage law and develops the theme in four parts. The 1st part (introduction) briefly reviews the history of the cabotage law and the country's current state of maritime shipping. The 2nd part (framework) presents three alternative courses of action, viz; (1) maintain the present cabotage law; (2) repeal the only ASEAN members to enter the local shipping industry. The 3rd part (discussion) expounds on the positive impact of each alternative and the last part (conclusion) presents the recommendation.